Pemberdayaan Masyarakat Melalui Public Private Partnership Bagi Peningkatan Pariwisata Desa Warnasari Kecamatan Pangalengan Kabupaten Bandung - Ine Mariane; Soleh Suryadi; Taqwaty Firdausijah; Rizki Ilhami (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
The main problem responded by partners is Karang Taruna as a business effort in Warnasari, one of which has not yet formed a commitment to make partnerships in planning in its area, because of the lack of resources and capital owned.The purpose of this community service program is to educate business actors related to the potential of existing agrotourism with the resources needed to build partnerships through private-public partnerships needed to develop existing tourism potential.The methodology of implementation in community service is divided into 3 (three) The result of community service activities in the village of Warnasari, Pangalengan Sub-district, Bandung Regency, was to build a public private partnership so that forming an MOU also gained the ability to manage tourism in the village of Warnasari, Pangalengan District, Bandung Regency.The impact of community service activities is the assistance of youth organizations as an aid to businesses and village apparatus in developing existing potential through private public partnerships developed by the MOU.The benefit of community service activities is the achievement of the welfare of the people of Warnasari Village, Pangalengan District, Bandung Regency, with tourism support in the area.